The Integration of Islamic Religious Education and Learning Technology in The Digital Era - Ibtisamah Khoirunnisaa; Muhammad Wildan Shohib (Universitas Muhammadiyah Surakarta, 2025)
The advancement of digital technology has significantly transformed the educational landscape, including the teaching and learning of Islamic Religious Education. Consequently, integrating technology has become an essential requirement to ensure that learning remains relevant and effective in the digital era. This study aims to analyze the urgency of technology integration in Islamic Religious Education, identify the challenges encountered in its implementation, and explore strategies to optimize the use of technology while maintaining Islamic values. This research employs a qualitative approach using a library research method. Data were collected through a systematic review of relevant literature, including books, peer-reviewed journal articles, conference proceedings, and academic documents related to Islamic Religious Education, educational technology, and digital literacy. The data were analyzed using descriptive qualitative techniques through classification, comparison, examination, and synthesis of findings to obtain a comprehensive understanding. The results indicate that technology integration in Islamic Religious Education can enhance students’ learning motivation, active participation, and understanding of Islamic values through digital media, online learning platforms, and blended learning models. Nevertheless, several challenges remain, including limited digital literacy among teachers and students, inadequate infrastructure, digital distractions, and the risk of misinterpreting Islamic teachings due to unreliable online information. Therefore, this study emphasizes the importance of sustainable strategies, such as improving teachers’ digital competencies, strengthening students’ digital literacy, applying prudent learning management, and fostering collaboration among schools, teachers, and parents to ensure effective, meaningful, and value-based integration of technology in Islamic Religious Education.